PEMBUATAN MOBILE CONTROLLING SYSTEM PADA INSTANSI PEMERINTAH KOTA SURABAYA - Evin Cintiawan; Daniel Hary Prasetyo; Daniel Soesanto (CALYPTRA, 2018)
e-Controlling is one of the sub-systems in Government Resources Management System (GRMS) that is used to monitor the plans and realizations of Government’s activity. In practical, e-Controlling has a feature to see the financial and monitoring reports. Problems encountered in the e-Controlling system is the complexity of the data table that is provided by the system when it is opened in mobile devices by the users. By the development of Mobile Controlling System, it is expected to be able to summarize all the data needed in a new simple display format. The testing and validation results received from the management and the administrator reveal a conclusion that Mobile Controlling System has a simple display format and can make user understands the data’s showed in the monitoring reports faster.